Implementing the routine immunisation data module and dashboard of DHIS2 in Nigeria, 2014–2019. Issue 7 (21st July 2020) - Shuaib, Faisal; Garba, Abdullahi Bulama; Meribole, Emmanuel; Obasi, Samuel; Sule, Adamu; Nnadi, Chimeremma; Waziri, Ndadilnasiya Endie; Bolu, Omotayo; Nguku, Patrick M; Ghiselli, Margherita; Adegoke, Oluwasegun Joel; Jacenko, Sara; et al.
Abstract : In 2010, Nigeria adopted the use of web-based software District Health Information System, V.2 (DHIS2) as the platform for the National Health Management Information System. The platform supports real-time data reporting and promotes government ownership and accountability. To strengthen its routine immunisation (RI) component, the US Centers for Disease Control and Prevention (CDC) through its implementing partner, the African Field Epidemiology Network-National Stop Transmission of Polio, in collaboration with the Government of Nigeria, developed the RI module and dashboard and piloted it in Kano state in 2014. The module was scaled up nationally over the next 4 years with funding from the Bill & Melinda Gates Foundation and CDC. One implementation officer was deployed per state for 2 years to support operations. Over 60 000 RI healthcare workers were trained on data collection, entry and interpretation and each local immunisation officer in the 774 local government areas (LGAs) received a laptop and stock of RI paper data tools. Templates for national-level and state-level RI bulletins and LGA quarterly performance tools were developed to promote real-time data use for feedback and decision making, and enhance the performance of RI services. By December 2017, the DHIS2 RI module had been rolled out in all 36 states and the Federal Capital Territory, and all states now report their RI data through the RI Module. All states identified at least one government DHIS2 focal person for oversight of the system's reporting and management operations. Government officials routinely collect RI data and use them to improve RI vaccination coverage. This article describes the implementation process—including planning and implementation activities, achievements, lessons learnt, challenges and innovative solutions—and reports the achievements in improving timeliness and completeness rates.